A Comparative Study of the Physico-Chemical Properties and Methylene Blue Adsorption Behaviour of Fly Ash, Nano-Oxides and the Composite Materials of Nano-Oxides and Fly Ash - Ayanda, Olushola S; Fatoki, Olalekan S; Adekola, Folahan A; Ximba, Bhekumusa J; Tijani, Jimoh O; Petrik, Leslie F (International Journal of Chemistry and Materials Research, 2014)
In this present study, composite materials involving fly ash produced from coal combustion and nano-oxides were prepared. The nature, morphology and properties of the precursors and the composite materials were determined by modern instrumental analytical techniques such as carbon, nitrogen and hydrogen (CNH) analysis, Brunauer–Emmett–Teller (BET) surface area and porosity analysis, scanning and transmission electron microscopy, and x-ray diffraction. Particle size distribution, ash content, pH and point of zero charge were also investigated. The adsorption kinetics of methylene blue (MB) onto these adsorbents was examined. Experimental results showed that the composition of fly ash and nano-oxides contributed to the development of intergranular voids and crevices with high surface and micropore areas that enhanced the adsorption of MB from an aqueous solution. The adsorption of MB onto the precursors and the composite materials follow the pseudo-second order kinetic model.